THE MEDIATING EFFECT OF SELF EFFICACY ON ENTREPRENEURSHIP KNOWLEDGE ON STUDENT ENTREPRENEURIAL INTEREST AT VOCATIONAL STATE SCHOOL IN MOJOKERTO REGENCY - Maghfiroh, Maghfiroh; Kusdiyanti, Heny; Maharani, Satia Nur (PT. BATARI EDU CALYA, 2023)
Unemployment is one of the main problems that every country faces. When talking about unemployment, it means not only talking about social problems but also talking about economic problems. This research uses a quantitative approach with Partial Least Squares structural equation modeling (PLS-SEM) to predict and confirm the given hypothesis. This study used Google Forms for the data collection on Vocational State School students in the Mojokerto district. Four hundred respondents from the three schools used as the object of research constituted the entire sample. The results showed that Entrepreneurship Knowledge and self-efficacy can explain the interest in entrepreneurship. However, the Entrepreneurship Knowledge variable will have more influence on entrepreneurial interest, if reinforced with Self-efficacy as a mediating variable